Determinants of the Capital Structure in the Colombian Chemical Industry (2000)
This research aimed to find the determinants of the capital structure of Colombian companies in the chemical sector. For that, annual data was taken from 233 firms in the period ranging from 2009 to 2018, which allowed to build an unbalanced panel with 1980 observations. The results showed that profitability, growth, size, and liquidity are decisive in the decision of capital structure of firms in the chemical sector in Colombia.